"Economic Crisis and Poaching: Advice on Anti-Poaching Management from The Galician Shellfish Sector". Issue 12 (2nd December 2019) - Ballesteros, Hugo M.; Rodríguez-Rodríguez, Gonzalo
ABSTRACT: The aim of this work is to prove the significant relationship between the economic crisis and the increase of the shellfish poaching in Galicia (NW Spain) during the period 2008–2012. A relationship was observed between the "necessity" causes and the economic incentives as an explanation for shellfish poaching. The results achieved pointing out the importance to complete the coercive dissuasive methods in the fight against poaching using informal management mechanisms implemented in Galician shellfish communities, especially in co-managed contexts in which unemployment and necessity processes are identified.